2018
DOI: 10.5812/ijcm.60846
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Cutaneous Squamous Cell Carcinoma Epidemiology, Diagnosis, and Management

Abstract: Introduction: Cutaneous squamous cell carcinoma (CSCC) is the second most common type of skin cancer and its incidence continues to rise worldwide. While the majority of CSCCs have excellent prognosis, a subset have the propensity to cause poor outcomes. Evidence Acquisition: A thorough Pubmed search was done and a collection of CSCC-relevant articles were selected based on the expert opinion. Results: A number of high-risk factors have been identified including perineural invasion (PNI), desmoplastic growth p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 74 publications
1
7
0
1
Order By: Relevance
“…Robsahm et al, showed a significant increase in all anatomical locations (except ears in female) from 1963 -2011, and most cSCC occurred in the head and face area (7). Similar to our findings Kabir et al, declared that most tumor locations were associated with poor outcomes including the ear, cheek, lip, temple, and anogenital area (20). In our study, there was no significantly increase in age frequency in 2015 to 2016, maximum age for cSCC was 95 and it was higher than the Robsahm et al, investigation, which had an age group 70 -79 years (7).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Robsahm et al, showed a significant increase in all anatomical locations (except ears in female) from 1963 -2011, and most cSCC occurred in the head and face area (7). Similar to our findings Kabir et al, declared that most tumor locations were associated with poor outcomes including the ear, cheek, lip, temple, and anogenital area (20). In our study, there was no significantly increase in age frequency in 2015 to 2016, maximum age for cSCC was 95 and it was higher than the Robsahm et al, investigation, which had an age group 70 -79 years (7).…”
Section: Discussionsupporting
confidence: 90%
“…According to these investigations, this study tries to notice the risk factors. (20). The rate did not increase significantly based on anatomical locations in 2015 and 2016 and the highest frequency of anatomical location of the tumor was nose and scalp.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Other risk factors include ionizing radiation, immunosuppression, chronic inflammation, arsenic exposure, human papillomavirus, and genetic disorders. [ 5 ] In his case, chronic inflammation occurred due to his neglected facial nonhealing wound. His presentation was consistent with high-risk cSCC,[ 6 ] which usually requires multidisciplinary approach.…”
Section: Discussionmentioning
confidence: 99%
“…Being the second most common form of skin cancer, squamous cell carcinoma (SCC) was mainly caused by cumulative ultraviolet exposure in white populations, while the most predisposing conditions of SCC were scarring processes and chronic inflammation in other populations. 1,2 This malignant transformation of chronic wounds or scar tissues (mostly post-burn scars) is known as Marjolin's ulcer (MU), with a reported incidence rate from 0.77% to 2%. [3][4][5] Once the malignancy develops, it tends to be more aggressive and is associated with a higher risk of metastasis compared with sun-induced SCC in Caucasians.…”
Section: Introductionmentioning
confidence: 99%